Molecular Detection of Endophytic Bacteria on Plantlet Tissue of Sugarcane - WIDAYATI, WIWIK EKO; WIDADA, JOKO; SOEDARSONO, JOEDORO (HAYATI Journal of Biosciences, 2009)
Endophytic bacteria live in plant host tissues without causing any symptoms. The aim of this study was to examine the indigenous endophytic bacteria on sugarcane plantlets produced from the young leaf cells by using tissue culture techniques. To detect the existence of endophytic bacteria in the plantlet tissue, a series of molecular method based on PCR were applied by using ribosomal intergenic spacer (RIS) primer followed by 16S rDNA partial sequence and single strand conformation polymorphism (SCCP). The results showed that the molecular method could detect the existence of bacteria in the tissues. Using the same methods, the bacteria were also found in other developmental stages of sugarcane (explants, differentiated tissues and callus). Key words: endophytic bacteria, PCR, RIS, 16S rDNA, SSCP